PERKEMBANGAN TAFSIR TIMUR TENGAH ZAMAN NABI SAMPAI KONTEMPORER - Maulana, Maulana (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2020)
The scholars sincerely and diligently continue to explore the meaning behind the existing verses. Thousands of books of interpretation have been written in their hands, with various schools of interpretation, methods and styles. The schools of interpretation such as the interpretation of bi al-ma'tsur or ar-Riwayah, the interpretation of bi al-ijtihadi or dirayah and the interpretation of bi isyari. Likewise, the patterns that color their books are linguistic, fiqh, tasawuf, social (al-Adab al-Ijtima'i), kalam (iqtiqadi), philosophy, tarbawi, morality and science ('ilmi). While the methods used by the commentators include: Tahli, Ijmali, muqaran, and maudu'i. The history of the development of interpretation from time to time. At the time of the Prophet and his companions, the interpretation had not been recorded properly, even the interpretation was still mixed with the traditions of the Prophet. At the time of the tabi'in and tabi' tabi'in the interpretation of the Koran began to develop rapidly. This was marked by the establishment of commentary study centers in Mecca, Medina and Kufa. In contemporary times the study of the study of the Koran is in accordance with the conditions of its interpreters. This is because in contemporary times it contains the paradigm that the Koran Salih li kulli era wa eats. This assumption implies that the socio-religious problems in the contemporary era will still be answered by the Qur'an by contextualizing interpretations continuously.